In Vitro Evaluation of Hen Eggshells Addition in Rice Husk on Litter Properties - Afnan, Rudi; Idana, Danar Bias; Yani, Ahmad (ANIMAL PRODUCTION, 2018)
Abstract. Ammonium (NH3) is released from uric acid of chicken feces. Good management practices are required to depress ammonium concentration in a litter. Several research findings showed that application of CaCO3 (calcium carbonate) can decrease ammonium concentration in a litter. Eggshell as a by-product of hennery (hen stable) and hatchery is mainly constructed from CaCO3. This research aimed to evaluate the addition of hen eggshell powder at different concentration in litter on water content, pH, microorganism, and NH3 concentration of litter. Rice husk as litter material, hen eggshell powder at a concentration of 0%, 5%, 10%, and 15% and hen manure were thoroughly mixed. After 24 hours, the concentration of water content, pH, microorganisms amount and NH3 in each treatment were measured. This research was completely randomized designed with 3 repetitions. Results showed the progressive addition of hen eggshell powder in litter until 15% increased pH and decreased water content, number of microorganisms and NH3 concentration. The addition of 15% hen eggshell powder in litter revealed best litter properties.Keywords:Â  ammonium, hen eggshell, litter, pH, water content